Peculiarities of the influence of psychological characteristics of boys and girls of different age groups on the formation of the need for achieving success - Круцевич, Тетяна; Марченко, Оксана (Slobozhanskyi Herald of Science and Sport, 2018)
Tetiana Krutsevych & Oksana Marchenko In the article aspects of the gender approach in physical education of schoolchildren are considered. Purpose: studying the influence of the psychological characteristics of the personality of schoolchildren of different age groups on the formation of the need to achievements. Materials & Methods: the study was conducted with a contingent of schoolchildren of grades 3–11. The total number of respondents was 628 people (young men – 282, girls – 346), of which 126 respondents (97 boys and 29 girls) are engaged in a certain sport. Standardized testing using S. Bem's method "Masculinity – Femininity" was used, a test and a questionnaire by Yu. M. Orlov "Need for Achievements", methods of mathematical statistics. Results: level of the need to achieve the success of schoolchildren of different age groups was studied, the gender type of the respondents' personality was determined. The relationship between the level of the need to achieve the success of schoolchildren and the features of their psychological sex was determined. Conclusion: differences in the levels of the need to achieve success for boys and girls of different age groups, who are engaged and do not go in for sports, are revealed. It is shown that it is necessary to consider the gender approach in education not from the point of view of a gender policy providing equal rights for men and women, but from the point of view of studying their psychosocial characteristics for creating adequate organizational and methodological conditions in the process of physical education.